Macronutrient intake as a prospective predictor of depressive symptom severity: An exploratory study with adolescent elite athletes - Gerber, M.; Jakowski, S.; Kellmann, M.; Cody, R.; Gygax, B.; Ludyga, S.; Müller, C.; Ramseyer, S.; Beckmann, J. (Psychology of Sport and Exercise, 2023)
Background Appropriate availability of macro- and micronutrients has an important impact on cognitive performance, mood and mental health. Although the critical role of nutrition for elite athletes` performance was recognized early on, little is known about whether consumption of specific macronutrients (carbohydrates, proteins, fat) predict the development of future depressive symptoms in adolescent elite athletes.